ANALISIS KESALAHAN MAKHRIJUL HURUF SANTRI MADRASAH AS-SALAM - Nanang Kosim; Ade Arip Ardiyansah; Sandi Aryawan (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
Arabic language learning begins with the pronunciation of Arabic letters (hijaiyah) due to the differences in phonetic systems between Indonesian and Arabic, which often lead to pronunciation errors, especially when reading the Qur'an. This study aims to identify pronunciation errors among TPA students and explore solutions through alternative teaching methods, focusing on students from Madrasah As-Salam Sukajadi Bandung, divided into two groups. The study employs a qualitative approach with a case study method. Techniques such as observation, interviews, and evaluations were used to gather case study data. Data were analyzed continuously from the start to the end of the study, involving data collection, identification, classification, frequency analysis of errors, identification of error areas, and error correction. Based on the discussion and data analysis, the most frequent errors among Madrasah As-Salam students occurred in pronouncing the letters ء, ف, and ش for Iqra students, and ق, ف, and ع for Qur'an-reading students. To address these errors, the study implemented the attartil method, which showed significant improvements. For Iqra students, the error rate for pronouncing ف decreased from 90% to 40%, ء from 80% to 20%, and ش from 70% to 20%. Meanwhile, for Qur'an-reading students, the error rate for pronouncing ف dropped from 35.75% to 21.5%, ق from 41.65% to 23.85%, and ع from 34.05% to 18.20%.